2021
DOI: 10.1002/jcp.30628
|View full text |Cite
|
Sign up to set email alerts
|

Lnc‐CPLC promotes the progression of colorectal cancer via regulating ZBTB34 by competitively binding miR‐4319

Abstract: Long noncoding RNAs (lncRNAs) have been considered as regulatory molecules that play crucial roles in diverse biological processes, including the regulation of tumor progression. However, in colorectal cancer (CRC), due to the complex regulatory relationships involved in lncRNAs, the details of the specific mechanism still need to be elucidated. To discover the key regulatory role of lncRNA in CRC, we used bioinformatics analysis methods for preliminary screening. Through the combination of in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Typically, lncRNAs act via target molecules [ 39 ], such as lncPOP1-1, that promotes cisplatin resistance in squamous cell carcinoma, which occurs in the neck, by interacting with MCM5 [ 40 ]. In addition, lncCPLC promotes colorectal resistance by regulating cancer progression via interaction with ZBTB [ 41 ]. At the same time, some lncRNAs in OC have also been reported to control OC resistance [ 42 ] or autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, lncRNAs act via target molecules [ 39 ], such as lncPOP1-1, that promotes cisplatin resistance in squamous cell carcinoma, which occurs in the neck, by interacting with MCM5 [ 40 ]. In addition, lncCPLC promotes colorectal resistance by regulating cancer progression via interaction with ZBTB [ 41 ]. At the same time, some lncRNAs in OC have also been reported to control OC resistance [ 42 ] or autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, lncRNAs act via target molecules [39] , such as lncPOP1-1, that promotes cisplatin resistance in squamous cell carcinoma, which occurs in the neck, by interacting with MCM5 [40] . In addition, lncCPLC promotes colorectal resistance by regulating cancer progression via interaction with ZBTB [41] . In the present study, we demonstrated that SLC25A21-AS1 was widely presented in the nucleus and cytoplasm, with a more abundant accumulation in the cytoplasm, suggesting that it likely functions at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration was assessed using a wound scratch healing assay using the previously described protocol. 23 , 24 First, monolayer cells were prepared. The cell density was 5 ~ 10 × 10 5 cells/ml were placed in 24 well plates (500 UL per well), and 10% fetal bovine serum was added to RMPI 1640 medium, cultured for 16 ~ 24 h to form monolayer cells.…”
Section: Methodsmentioning
confidence: 99%